- Download PDF
1 Answer | Add Yours
Expand right side. Apply the property of logarithm which is `log_b M/N=log_b M - log_b N` .
`y=log_10 (x^2-1) - log_10 x`
To determine y', take the derivative of each term.
`y'=(log_10 (x^2-1))' - (log_10x)'`
Apply the formula of derivative of logarithmic functions which is `(log_b u)' = (log_b e)/u*u'` .
`y'=(log_10 e)/(x^2-1)*(x^2-1)' - (log_10 e)/x*x'`
` y'=(log_10 e)/(x^2-1)*2x - (log_10 e)/x*1 `
`y'=(2xlog_10 e)/(x^2-1)-(log_10 e)/x`
Hence, the derivative of the given function is `y'=(2xlog_10 e)/(x^2-1)-(log_10 e)/x` .
We’ve answered 323,775 questions. We can answer yours, too.Ask a question